Parent‐of‐origin control of transgenerational retrotransposon proliferation in Arabidopsis. (9th July 2013) - Reinders, Jon; Mirouze, Marie; Nicolet, Joël; Paszkowski, Jerzy
Abstract : Retrotransposons are ubiquitous mobile genetic elements constituting a major part of eukaryotic genomes. Yet, monitoring retrotransposition and subsequent copy number increases in multicellular eukaryotes is intrinsically difficult. By following the transgenerational accumulation of a newly activated retrotransposon EVADE ( EVD ) in Arabidopsis, we noticed fast expansion of activated elements transmitted through the paternal germ line but suppression when EVD ‐active copies are maternally inherited. This parent‐of‐origin effect on EVD proliferation was still observed when gametophytes carried mutations for key epigenetic regulators previously shown to restrict EVD mobility. Therefore, the main mechanism preventing active EVD proliferation seems to act through epigenetic control in sporophytic tissues in the mother plant. In consequence, once activated, this retrotransposon proliferates in plant populations owing to suppressed epigenetic control during paternal transmission. This parental gateway might contribute to the occasional bursts of retrotransposon mobilization deduced from the genome sequences of many plant species. Parent‐of‐origin control of transgenerational retrotransposon proliferation in Arabidopsis : The authors of this study observe parent‐of‐origin effects regulating retrotransposition in Arabidopsis characterized by expansion and suppression in the paternal and maternal germ line, respectively. The parent‐of‐origin effect was still observed when gametophytes carried mutations for key epigenetic regulators indicating that the suppressive regulation occurs in the maternal sporophytic tissues.